Improving student learning outcomes in sports massage and sports injury prevention handling courses through a project based learning model using active learning methods - Nugraha, Ugi; Anjanika, Yonifia; Suhartini, Sugih (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Problems: The massage course is one of the practical courses that students in the Department of Sports and Health Education must take with the requirement of passing basic anatomy and exercise physiology courses. Based on observations of 4th semester Sports Coaching students in the Theory and Practice lecture on the Sports Massage Handling Sports Massage Handling Sports Injury Prevention course, the learning method used is still conventional, namely the lecturer still dominates the learning process. Passive learning methods are certainly less effective and do not involve students in teaching and learning activities so that students tend to be passive. Purpose: The aim of this research is to determine the improvement in student results in the Sports Massage and Sports Injury Prevention courses through the Project Based Learning (PBL) Model Using Active Learning Methods. Methods: This type of research is classroom action research, with two cycles. The instrument used in this research was the Sports Massage course and the treatment of sports injury prevention. The subjects in this research were 4th semester Sports Coaching students, totaling 33 students. The data analysis technique used is descriptive statistics with percentages. Result: Based on the research results, the test results for the success of sports massage practice were obtained using the Student Active Learning Method approach. The Project Based Learning (PBL) model achieved achievement in pre-action, only 7 students (21.21%) completed, in cycle 1 results 18 students (54.54%) completed with an average score of 57.58%, and in cycle 2 saw an increase in learning outcomes as many as 29 students (87.88%) successfully completed it. Conclusion: Learning outcomes in cycle II obtained from reflection: students have started to get used to learning that uses a project or practice approach with injury cases, students are more active and creative in the learning process.